2018
DOI: 10.1152/japplphysiol.00580.2018
|View full text |Cite
|
Sign up to set email alerts
|

CT-measured lung air-trapping is associated with higher carotid artery stiffness in individuals with chronic obstructive pulmonary disease

Abstract: Early stages of chronic obstructive pulmonary disease (COPD) are characterized by the loss and narrowing of terminal bronchioles in the lung, resulting in “air-trapping,” often occurring before overt emphysema manifests. Individuals with an airway-predominant phenotype of COPD display extensive lung air-trapping and are at greater cardiovascular disease (CVD) risk than COPD patients with an emphysema-predominant phenotype. We hypothesized that the degree of computed tomography (CT)-quantified lung air-trapping… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Numerous studies have found that PWV is abnormally high in COPD patients [ 58 , 59 ]. Arterial stiffness, as measured by PWV, was independently associated with the severity of emphysema [ 60 ] and airway obstruction [ 59 , 61 , 62 , 63 , 64 ]. Furthermore, it was established by studying twins that the link between lung function and arterial stiffness is not genetically determined.…”
Section: Oxidative Stress—a Link Between Copd and Cardiovascular Como...mentioning
confidence: 99%
“…Numerous studies have found that PWV is abnormally high in COPD patients [ 58 , 59 ]. Arterial stiffness, as measured by PWV, was independently associated with the severity of emphysema [ 60 ] and airway obstruction [ 59 , 61 , 62 , 63 , 64 ]. Furthermore, it was established by studying twins that the link between lung function and arterial stiffness is not genetically determined.…”
Section: Oxidative Stress—a Link Between Copd and Cardiovascular Como...mentioning
confidence: 99%
“…The exact mechanism by which COPD enhances risk of MACEs is not completely clear, but could be explained by airway and systemic inflammation resulting in over spilling of inflammatory cytokines in circulation leading to atherosclerosis. Also, COPD patients frequently demonstrate myocardial inflammation, arterial stiffness and endothelial dysfunction, intensified during acute exacerbations, possibly owing to “blood” inflammation and elastin degradation (57). Moreover, patients with COPD experience dynamic (and even static) hyperinflation, which may increase end diastolic pressures in the heart, and impair both right and left ventricular contractility that can further increase CV risk (8).…”
mentioning
confidence: 99%